Central European parasitic flatworms of the Cyclocoelidae Stossich, 1902 (Trematoda: Plagiorchiida): molecular and comparative morphological analysis suggests the reclassification of Cyclocoelum obscurum (Leidy, 1887) into the Harrahium Witenberg, 1926 - Sitko, Jiljí; Bizos, Jiří; Heneberg, Petr (Parasitology, 2017)
Cyclocoelidae Stossich, 1902 are medium-sized to large digenean bird parasites. Although these parasites bear few visible autapomorphic signs, and their diagnostic characters are unstable in response to the pressure applied during preparation, the numerous hitherto suggested re-classifications within the family have not been supported by any molecular analysis. We analyse here cyclocoelids found during the extensive examination of central European birds performed from 1962 to 2016, provide comparative measurements, host spectra, prevalence and intensity, and provide and analyse sequences of four DNA loci of five of the cyclocoelid species. Cyclocoleum Brandes, 1892 appears paraphyletic; thus we suggest the re-classification of Cyclocoleum obscurum (Leidy, 1887) as Harrahium obscurum (Leidy, 1887) Sitko and Heneberg comb. n. Molecular phylogenetics questioned also the validity of Cyclocoelinae Stossich, 1902 and Hyptiasminae Dollfus, 1948, which formed a single clade, whereas Allopyge Johnston, 1913, Prohyptiasmus Witenberg, 1923 and Morishitium Witenberg, 1928 formed another clade. Haematotrephinae Dollfus, 1948 are newly characterized as having a pretesticular or intertesticular ovary that forms a triangle with the testes. Analyses of non-European genera of the Cyclocoelidae and an examination of the position of families within Echinostomata La Rue, 1926 are needed.
Keywords: Bird Diseases; RNA ribozomální 18S; Gene Expression Regulation, Enzymologic; RNA, Helminth; Phylogeny; Birds; Trematoda; Europe; zvířata; druhová specificita; DNA, Helminth; ptáci; infekce červy třídy Trematoda; nemoci ptáků; mezerníky ribozomální DNA; regulace genové exprese enzymů; DNA, Ribosomal Spacer; Species Specificity; Electron Transport Complex IV; Evropa; respirační komplex IV; ženské pohlaví; RNA helmintů; Animals; fylogeneze; RNA, Ribosomal, 18S; DNA helmintů; Trematode Infections; Female